Improving University Students' Teachers’ Comprehension of School Management Concepts through Flipped Learning - Putrawan I Made (Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
Conventional instruction, which remains focused on content delivery, tends to position students as passive recipients of information with limited opportunities to construct an understanding of concepts independently. This situation highlights the need for innovative instructional strategies that optimize student engagement in grasping concepts related to institutional or corporate management. This study aims to analyze the effectiveness of the flipped learning strategy and evaluate its contribution to enhancing students' understanding of institutional or corporate management concepts. The study employs the Research and Development (R&D) method, utilizing a development design based on the stages outlined by Borg and Gall. The participants consisted of 73 pre-service teacher students enrolled in an institutional or corporate management course. Data were collected through a concept-understanding instrument covering three dimensions expressing, categorizing, and summarizing comprising 35 items that met reliability criteria. Data analysis used descriptive statistics and t-tests to determine differences in students' comprehension levels before and after implementing flipped learning. The results indicate that the flipped learning strategy significantly improved students' understanding after using the developed learning package. Consequently, flipped learning serves as an innovative instructional alternative that fosters active, independent, and meaningful learning. The study's findings contribute to the development of technology-based instruction aimed at enhancing the quality of learning in higher education.